2009
DOI: 10.1088/2040-8978/12/1/015705
|View full text |Cite
|
Sign up to set email alerts
|

The N-slit interferometer: an extended configuration

Abstract: An N-slit interferometer is demonstrated with an intra-interferometric propagation path of up to 35 m. The configuration of the N-slit interferometer was extended to its maximum as allowed by the available grating, laser wavelength, and dimensions of the digital detector. Interferometric computations, based on the application of Dirac’s notation, were successfully used to predict the structure and divergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 10 publications
(21 reference statements)
1
18
0
Order By: Relevance
“…At D 1 the superposition of the diffraction signal over the interferometric distribution is beautifully predicted as illustrated in Figure 20.9. Previously, it was demonstrated that insertion of a conventional thin and highly transparent beam splitter into the intra-interferometric path led, as expected (see Chapter 11), immediately to a catastrophic collapse of the interferometric character or signal (Duarte, 2002(Duarte, , 2005Duarte et al, 2010). Furthermore, at D 3 , the silk fiber produces almost no disturbance when placed between slits and tends to only very slightly modify the whole interferometric distribution when positioned at the center of one of the slits (Figure 20.11).…”
Section: Comparison Between Theoretical and Measured N-slit Interferomentioning
confidence: 54%
“…At D 1 the superposition of the diffraction signal over the interferometric distribution is beautifully predicted as illustrated in Figure 20.9. Previously, it was demonstrated that insertion of a conventional thin and highly transparent beam splitter into the intra-interferometric path led, as expected (see Chapter 11), immediately to a catastrophic collapse of the interferometric character or signal (Duarte, 2002(Duarte, , 2005Duarte et al, 2010). Furthermore, at D 3 , the silk fiber produces almost no disturbance when placed between slits and tends to only very slightly modify the whole interferometric distribution when positioned at the center of one of the slits (Figure 20.11).…”
Section: Comparison Between Theoretical and Measured N-slit Interferomentioning
confidence: 54%
“…This question can be answered empirically. Further, the effect of severe clear-air turbulence detected at D 〈x|j〉 = 7.235 m, for the c (N = 4) character, is shown in Figure 11.17 (Duarte et al, 2010). Now, by contrast we consider Figure 11.16 where the distortions due to mild clear-air turbulence detected at D 〈x|j〉 = 7.235 m, for the c (N = 4) character, are illustrated (Duarte, 2009).…”
Section: Clear-air Turbulencementioning
confidence: 96%
“…The overall ruled area is 50 mm × 50 mm (Duarte et al, 2010). For instance, one of the gratings utilized has 570 μm slits separated by 570 μm isles, and the other grating has 1000 μm slits separated by 1000 μm isles.…”
Section: N-slit Interferometer For Secure Free-space Optical Communicmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported on an N-slit interferometer with an intra interferometric path length of 35 m [1].…”
Section: Introductionmentioning
confidence: 99%